2016
DOI: 10.1186/s13018-016-0456-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of recent guideline changes on aspirin prescribing after knee arthroplasty

Abstract: BackgroundPrior to 2012, the American Academy of Orthopaedic Surgeons (AAOS) and American College of Chest Physicians (ACCP) differed in their recommendations for postoperative pharmacologic venous thromboembolism prophylaxis (VTEP) after total joint arthroplasty. More specifically, aspirin (ASA) monotherapy was not endorsed by the ACCP as an acceptable prophylaxis. In 2012, the ACCP supported ASA monotherapy compared with no prophylaxis. Our aim was to investigate the impact of the convergence of ACCP and AAO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 45 publications
1
15
0
6
Order By: Relevance
“…Utilization trends for these agents are not well-studied. In one single-institution study, the rates of prescribing aspirin as the VTE agent increased after the convergence of the American Academy of Orthopaedic Surgeons and the American College of Chest Physicians guidelines, while all other agents including factor Xa inhibitors decreased [35]. In our study, the increase in factor Xa inhibitor use likely followed the results of the RECORD3 and RECORD4 trials.…”
Section: Discussionsupporting
confidence: 61%
“…Utilization trends for these agents are not well-studied. In one single-institution study, the rates of prescribing aspirin as the VTE agent increased after the convergence of the American Academy of Orthopaedic Surgeons and the American College of Chest Physicians guidelines, while all other agents including factor Xa inhibitors decreased [35]. In our study, the increase in factor Xa inhibitor use likely followed the results of the RECORD3 and RECORD4 trials.…”
Section: Discussionsupporting
confidence: 61%
“…A recent poll of over 1200 attendees of the 2016 meeting of the American Association of Hip and Knee Surgeons, showed that over 80% orthopedic surgeons use aspirin as the main VTE prophylaxis [24]. In the same vein, a retrospective analysis in the United States reported that while healthcare provider utilization of aspirin has increased (55.6% post-2012 vs pre-2012 13.9%, P < .001), there has not been an apparent change in VTE risk [25]. Additionally, over the last 5-10 years early discharge and outpatient protocols have been adopted, as well as a concomitant reduction in length of stay (LOS) [26e29].…”
mentioning
confidence: 99%
“…6,17 Our previous retrospective cohort study which similarly investigated thromboembolic risk in a large nationally representative sample of patients receiving aspirin compared with anticoagulation after knee or hip replacement surgery between 2009 and 2012 in the USA found that aspirin-only was administered in 7.5-8% of cases, 6 while this proportion increased to more than 27% in our current study that covered a timeframe after publication of the updated American College of Chest Physicians (ACCP) guidelines. Similarly, a recent retrospective chart review of 329 patients undergoing knee arthroplasty at 2 tertiary care centers found that the proportion of patients receiving monotherapy with aspirin for postoperative thromboprophylaxis increased from 4.6 to 44.4% in the periods before and after the publication of ACCP guidelines in 2012 18 ; in these updated guidelines, the use of aspirin as a sole thromboprophylactic agent after knee or hip arthroplasty was newly endorsed and hence, consensus was reached with the recommendations made by the American Academy of Orthopedic Surgeons (AAOS). 1,19,20 It is notable that the Numbers are presented as n (%).…”
Section: Discussionmentioning
confidence: 99%